Prática empreendedora parental: o olhar da teoria da prática social sobre o fenômeno do empreendedorismo materno - Passos, Janaína Sousa Loureiro (2019)
The study of female entrepreneurship is not new in the academic literature, recognizing that the opening of businesses does not bring challenges and motivations in an equal way for men and women (KHAN; ROWLANDS, 2018). As a consequence of this movement, the recognition of a group of people, usually women, who open businesses in a context where they seek to integrate the demands of motherhood and entrepreneurship can be recognized. In this sense, it is faced with a new expression in academic studies on entrepreneurship: mumpreneurship or, in Portuguese, maternal entrepreneurship. Observing that this phenomenon has been gaining space in the media and in society, the call for academic studies on the subject is the starting point of this thesis. After exploring readings on maternal entrepreneurship and readings on the theory of social practice, I defend the thesis that, behind this phenomenon, there is a practice that I call Parental Entrepreneurial Practice. That said, based on Theodore Schatzki's Theory of Social Practice, the present work seeks to understand how, and if it does, Parental Entrepreneurial Practice. The research method chosen to conduct this work was Autoetnografia, considering that it is a work carried out by a mother who started a company where she prioritizes the reconciliation of her entrepreneurial activity with the care of her children. For this, a concept of Parental Entrepreneurial Practice was developed theoretically before going to the field and an empirical concept after research. After conducting this research, the empirical findings showed that, unlike the concept theoretically elaborated, there is an arrangement of practices that form the phenomenon of parental entrepreneurial practice. Corroborating with the literature of the theory of social practice by Schatzki (2012), it was possible to perceive empirically an arrangement where the practices contained in it reveal the relations of causality, prefiguration, constitution, intentionality and intelligibility, explained and discussed throughout the work. The research findings revealed what is the parental entrepreneurial practice (an arrangement of practices) and what is the tele-affective structure that guides this arrangement, bringing possibilities for future research and discussions on the theme, demonstrated in the conclusions of the work.